Pembinaan Pelaku Usaha Perempuan Melalui Pelatihan Manajemen Usaha dan Keuangan Bagi Pelaku UMKM di Gampong Meuria Paloh Kota Lhokseumawe - Fuadi; Reza Juanda; Rani Puspita Ningrum; Munardi; Khairawati; Falahuddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The aim of this non-profit initiative is to find solutions to the problems faced by women entrepreneurs in the village of Meulia Paro, Lhoksumawe. Issues identified include lack of knowledge and motivation in online business, lack of understanding of financial management when running a business, lack of capital and knowledge when managing long-term assets, and lack of understanding of Islamic business ethics. etc. As a method of implementing this activity, we conduct preliminary observations, approaches based on social observations, examine issues, and find appropriate solutions. The implementation phase includes interaction, counseling and training for her MSME business people in Meuria Paloh Village. Evaluation is done by observing the economic agent again after the end of the philanthropic activity. The conclusions of this non-profit activity indicated that most of the training participants had limited knowledge and motivation for online business, poor understanding of Islamic business ethics, and poor financial management. I'm here. Therefore, this outreach can provide sustainable solutions for women entrepreneurs in Meulia Paro village, improve the quality of their business, understand Islamic business ethics and financial management, and expand the market for MSME products. is expected.